Past and Present Approaches to Diagnosis of Active Pulmonary Tuberculosis - Namuganga, Anna Ritah; Chegou, Novel N.; Mayanja-Kizza, Harriet (Frontiers in Medicine, 2021)
Tuberculosis disease continues to contribute to the mortality burden globally. Due to the several shortcomings of the available diagnostic methods, tuberculosis infection continues to spread and thus disease. The difficulty to obtain sputum among the very ill patients and the children also affects the quick diagnosis of tuberculosis disease. These challenges warrant investigating different sample types that can provide results in a short time. Highlighted in this review are the approved pulmonary tuberculosis diagnostic methods and ongoing research to improve its diagnosis.